Analysis of the use of keigo by native speakers in the Gifu Spring Golf Club environment in Japan - Diner, Lispridona; Pertiwi, Sindi Bina Ari Yaningsih (Japanese Research on Linguistics, Literature, and Culture, 2024)
Keigo is a variety of Japanese that expresses politeness used to respect the person you are talking. This study aims to determine the frequency of keigo use, differences in the frequency of keigo use by gender, and the situation of keigo use in the Gifu Spring Golf Club company environment. This research method uses quantitative and qualitative descriptive with a sample of 15 people. The results of this study show that (1) there are 3 types of keigo used, 75% of employees use sonkeigo, 67% of employees use kenjougo, 97% of employees use teineigo. The type of keigo that is always used is teineigo. (2) the use of sonkeigo is 80% of male employees, 68% of female employees, the use of kenjougo is 67.5% of male employees, 65.7% of female employees, the use of teineigo is 100% of male employees, 94.2 % female employees. With this, male employees are higher than female employees. (3) The situation of using keigo when employees at the reception, restaurant and masutaa speak directly in a polite form to respect customers.